The iterative turbo decoding algorithm has fixed points - Duan, L.; Rimoldi, B. (IEEE transactions on information theory, 2001)
It is shown that the iterative decoding algorithm proposed to decode "turbo codes" has fixed points regardless of the specific constituent codes and regardless of the noise variance of the additive white Gaussian noise (AWGN) channel.